The expression of HSP70 in skeletal muscle is not associated with glycogen availability during recovery following prolonged exercise in elite endurance athletes - Dalgaard, L. B.; Ørtenblad, N.; Hvid, L. G.; Gejl, K. D. (European Journal of Applied Physiology, 2022)
The 70-kDa heat shock protein (HSP70) is a ubiquitous molecular chaperone which is highly inducible by cellular stress such as exercise. To investigate the role of muscle glycogen content on the HSP70 expression, muscle glycogen was manipulated by consumption of either water (H2O) or a carbohydrate-enriched diet (CHO) during recovery from 4 h of glycogen-depleting cycling exercise in fourteen elite endurance athletes. Muscle biopsies were obtained pre- and post-exercise, and after 4 and 24 h of recovery, and analyzed for HSP70 mRNA expression, as well as HSP70 protein expression and muscle glycogen within the same skeletal muscle fibers using immunohistochemistry. Exercise reduced glycogen by 59 ± 10% (P < 0.0001). After 4 h of recovery, glycogen approached resting levels in the CHO group (86% of pre, P = 0.28) but remained suppressed in the H2O group (41% of pre, P < 0.001) (group × time interaction: P = 0.002). Importantly, both the HSP70 mRNA (+ 1.6-fold (+ 0.28/- 0.24), P = 0.02) and protein expression (+ 147 ± 99%, P < 0.0001) was substantially increased after exercise and remained elevated in both groups after 4 h of recovery, despite clear differences in muscle glycogen content. Thus, muscle glycogen content was not related to the variation in single fiber HSP70 expression at the 4-h time-point (r2 = 0.004). In conclusion, muscle HSP70 expression remained elevated during recovery from prolonged exercise in highly trained skeletal muscle, irrespective of muscle glycogen availability.